Clinical utility of thiopurine metabolite monitoring in inflammatory bowel disease and its impact on healthcare utilization in Singapore. Issue 10 (1st August 2022) - Yeo, Jia Qi; Cheen, Hua Heng McVin; Wong, Amanda; Lim, Teong Guan; Chowbay, Balram; Leong, Wai Fook; Wang, Chunyan; Salazar, Ennaliza; Chan, Webber Pak Wo; Kong, San Choon; Ong, Wan Chee
Abstract: Background and Aim: Thiopurines are recommended for maintenance of steroid‐free remission (SFR) in inflammatory bowel disease (IBD). Thiopurine metabolite monitoring (MM) is increasingly used in the West but remains novel in Singapore, with limited information on its therapeutic and economic benefits. Hence, this study aims to investigate MM's clinical utility and its impact on healthcare resource utilization in Singaporean IBD patients. Methods: A retrospective observational study was conducted at Singapore General Hospital outpatient IBD Centre. Patients with IBD, baseline MM during 2014–2017, and weight‐based thiopurine doses for ≥4 weeks were followed up for 1 year. Actions were taken to optimize therapy, and metabolite levels before and after the first action were documented. Outcomes assessed included SFR, no therapy escalation or surgery, healthcare resource utilization, and direct healthcare costs. Results: Ninety IBD patients (50 Crohn's disease, 40 ulcerative colitis) were included. Among them, 40% had baseline metabolite levels within therapeutic range, 31.1% sub‐therapeutic, 21.1% supra‐therapeutic, and 7.8% shunters. Repeated MM with subsequent dose optimization helped 67.2% of patients achieve therapeutic levels after 1 year. Overall, 87.8% of patients achieved SFR and 90% had no therapy escalation or surgery. Despite greater outpatient visits and laboratory investigations with MM, the median total healthcare costs at 1 year only increased marginally (S$6407.66 [shunters] vs S$5215.20 [supra‐therapeutic] vs S$4970.80 [sub‐therapeutic] vs S$4370.48 [control (within therapeutic range)], P  = 0.592). Conclusion: MM guided timely therapy escalation for non‐responders, identification of non‐adherence, and reversal of shunting. Therefore, it is a useful clinical tool to optimize thiopurines without significantly increasing healthcare costs. Abstract : Thiopurine metabolite monitoring (MM) is still a new strategy in Singapore with limited information on its therapeutic and economic benefits. Our study showed that MM is able to guide timely dose optimization and therapy escalation for nonresponders. MM also identifies and reverses shunting and addresses non‐adherence. It is a useful clinical tool without significantly increasing healthcare resource utilization and costs.